Workshop How to Register a Journal to the Directory of Open Access Journals (DOAJ) - Mardiana, Harisa (Edumedia Solution, 2023)
Promoting journals managed in DOAJ, it provides convenience as a curated online directory a community that indexes and provides access to managed journals to improve the journal. Â The data available in DOAJ are independent, and this community service is believed to guide journal managers regarding DOAJ indexing. The problem is that many scientific journals in Indonesia have yet to be indexed by DOAJ, which DOAJ provides all content free of charge without delays or user registration requirements and meets high-quality standards. This community service method uses three stages. The first stage is the preparatory stage of team coordination to determine collaboration, resource persons, and preparation of activities and events. The second stage follows up the implementation with activities in the form of lectures, discussions, questions and answers, and practice which aims to build insight into registering journals with DOAJ. The evaluation stage is carried out by giving questionnaires to seminar participants as respondents to get feedback from the organizers. The results were that 86.96% understood how to register scientific journals with DOAJ. Thus, it can be obtained an overview of the level of success in implementing community service related to participants' understanding of registering scientific journals with DOAJ.